The aesthetic formation of the duality of voice and silence in the performance of the Iraqi theatrical actor (Amal play as a model) (Al-Academy, 2025)
This study aims to deeply understand the (aesthetic formation) of the duality (sound and silence) in the theatrical actor’s performance by analyzing all the technical, aesthetic and psychological factors associated with (sound and silence) to reach a clear understanding of their impact on the actor’s performance and his success in communicating effectively with the audience. Therefore, New techniques will be highlighted to enhance the actor’s abilities in expressing thoughts and feelings through (voice and silence) in conveying the theatrical message, in addition to the importance of physical factors with physical language in feeding the actor’s performance of the character. This research will contribute to deepening our understanding of the actor’s tools that enhance the development of his abilities. Performance on stage .This is what was explained in the research chapters represented by the first chapter (methodological framework) and the second chapter, which consisted of the first topic (the aesthetic concept of duality of form and morphology) and the second topic (the effectiveness of sound and silence in acting performance), leading to the third chapter (research procedures), which included an analysis of the play (Hope) and Chapter Four (Results and Conclusions, including): 1- Both (Sound and Silence) clearly depict the psychological state of the two characters (Amal and Basem) through performative transformations on the physical and vocal levels. 2- The audio system intended to add a state of instability and stability to the physical system through the emotions of the two characters throughout the show.Keywords: form, beauty, sound, silence.